Normative Reconstruction of Trademark Dispute Resolution in Indonesia: Harmonizing First-to-File and Well-Known Mark Protection - Haryono Haryono; Sri Suneki; A. Rizal (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Trademark disputes in Indonesia reveal persistent tensions between the first-to-file principle and the protection of well-known marks. Although the constitutive registration system aims to ensure legal certainty, its rigid application has generated inconsistent judicial outcomes when confronted with internationally recognized trademarks. This study examines the normative weaknesses of Indonesia’s trademark dispute resolution framework and proposes a reconstructed legal model to harmonize registration-based protection with reputation-based recognition. This research employs a normative juridical method supported by statute, case, and comparative approaches. Primary legal materials include the Indonesian Trademark and Geographical Indications Law, relevant international instruments, and selected judicial decisions. Comparative analysis is conducted with Singapore, Malaysia, the European Union, and the United States to identify best practices in recognizing well-known marks. The findings indicate three principal deficiencies: the absence of clear standards for assessing distinctiveness, the lack of codified objective criteria for recognizing well-known marks, and insufficient statutory parameters for determining bad faith registration. These weaknesses contribute to fragmented judicial interpretations and reduced legal predictability. The study proposes normative reconstruction through the incorporation of measurable indicators—such as consumer recognition, duration of use, market share, and advertising intensity—alongside explicit formulation of bad faith criteria and strengthened jurisprudential consistency. Such reform is essential to enhance legal certainty, protect brand equity, align Indonesia with international intellectual property standards, and foster sustainable economic development in a globalized market.